2018
DOI: 10.5603/cj.a2017.0138
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of repolarization changes in supine versus upright body position

Abstract: Background: The impact of postural changes on various electrocardiography (ECG) charac-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Our finding of the association of beat-to-beat QT variability with the morphological instability (which, for simplicity's sake, we call "noise") of the source ECG tracing should not be interpreted as a suggestion that there are no beat-to-beat QT changes and that only morphology changes influence the beatto-beat measurements. Morphological ECG changes might also have valid biological basis [e.g., related to respiration (Noriega et al, 2012;Sadiq et al, 2021), posture (Markendorf et al, 2018), food intake (Täubel et al, 2019), mental stress (Hwang et al, 2018), and other external inputs and physiologic reflexes]. While some of these mechanisms might not be fast enough to contribute beat-to-beat changes in QT interval measurements, it seems clear that the measurement of the differences between individual beats and the global representative waveform is not FIGURE 14 | The residual reductions shown in this figure (A-D) are defined as values of relative decrease of intra-subject residuals of linear regressions SDQT calculated as proportions of intra-subject standard deviations of SDQT.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of the association of beat-to-beat QT variability with the morphological instability (which, for simplicity's sake, we call "noise") of the source ECG tracing should not be interpreted as a suggestion that there are no beat-to-beat QT changes and that only morphology changes influence the beatto-beat measurements. Morphological ECG changes might also have valid biological basis [e.g., related to respiration (Noriega et al, 2012;Sadiq et al, 2021), posture (Markendorf et al, 2018), food intake (Täubel et al, 2019), mental stress (Hwang et al, 2018), and other external inputs and physiologic reflexes]. While some of these mechanisms might not be fast enough to contribute beat-to-beat changes in QT interval measurements, it seems clear that the measurement of the differences between individual beats and the global representative waveform is not FIGURE 14 | The residual reductions shown in this figure (A-D) are defined as values of relative decrease of intra-subject residuals of linear regressions SDQT calculated as proportions of intra-subject standard deviations of SDQT.…”
Section: Discussionmentioning
confidence: 99%
“…Excitement, panic, worry, and posture change can all cause sympathetic excitement. Markendorf et al ( 31 ) reported that when the supine position was turned to the orthostatic position, the heart rate and the rate of T-wave inversion increased. Obata et al ( 32 ) reported that the QT interval was lower in orthostatic ECG than supine ECG (366.40 ± 35.00 ms vs. 382.30 ± 33.90 ms, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…В самое крупное исследование в этом области, проведенное среди 1 028 человек старше 18 лет, в том числе вошли пациенты, страдающие различными сердечно-сосудистыми заболеваниями, но не имеющие СУИQT, продолжительность интервала QTс в вертикальном положении была несколько ниже, чем в нашем исследовании (440 ± 28 мс), но здесь за вертикальное положение принималось положение сидя, что, возможно, обусловливает более низкие значения этого показателя. Авторы исследования сделали противоречивые выводы о том, E-mail: medalfavit@mail.ru что интервал QT можно быть оценен только в положении лежа, так как в вертикальном положении этот показатель удлиняется [13]. В работе, выполненной нами ранее по оценке изменений интервалов QT и QT с в ранний период ортостаза у юных элитных атлетов, мы не отметили достоверной разницы в продолжительности интервала QTс в ортостазе у детей, занимающихся и не занимающихся спортом [14].…”
Section: Discussionunclassified